Semiotika Lambang Bulan Bintang Bersinar Lima sebagai Media Dakwah Tuan Guru Kyai Haji Muhammad Zainuddin Abdul Madjid (Studi Kasus pada Organisasi Nahdlatul Wathan) - Irfan Hasbi (Universitas Islam Negeri Mataram, Indonesia, 2021)
This study aims to determine the semiotics of the five shining star moon symbol as a medium of propaganda for T.G.K.H. Muhammad Zainuddin Abdul Madjid in the Nahdlatul Wathan organization and to find out the history of the NW symbol and the practice of the meaning of the symbol at the socio-religious level. This research uses descriptive qualitative method. The data collection technique uses triangulation, which is a data collection technique that is a combination of various data collection techniques and existing data sources. The data analysis technique used is interactive analysis with four paths, namely data collection, data reduction, data presentation, and drawing conclusions. For the validity of the data, it was carried out through a data credibility test by means of triangulation of sources and triangulation of techniques. The results of this study indicate that the five shining star moon logo is designated to be the symbol of NW as a medium of propaganda for T.G.K.H. Muhammad Zainuddin Abdul Madjid with the blessing of his professor, Maulanasyaikh Hassan Muhammad Al-Masyath. After combining it with the study of Semiotics by Charles S. Peirce, the existence of the NW symbol is in accordance with the principles of Semiotics and the description of the meaning of the NW symbol has been found and applied to the fields of education, social and propaganda of Nahdlatul Wathan. Keywords: Semiotics, Media Da'wah, Nahdlatul Wathan. Penelitian ini bertujuan untuk mengetahui Semiotika lambang bulan bintang bersinar lima sebagai media dakwah T.G.K.H. Muhammad Zainuddin Abdul Madjid di organisasi Nahdlatul Wathan dan untuk mengetahui sejarah lambang NW serta praktik makna lambang tersebut pada tataran sosial keagamaan. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik pengumpulan data menggunakan triangulasi, yaitu teknik pengumpulan data yang bersifat penggabungan dari berbagai teknik pengumpulan data dan sumber data yang telah ada. Teknik analisis data yang digunakan ialah analisis interaktif dengan empat jalur, yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Untuk validitas data, dilakukan melalui uji kredibiltas data dengan cara triangulasi sumber dan triangulasi teknik. Hasil penelitian ini menunjukkan bahwa logo bulan bintang bersinar lima ditetapkan menjadi lambang NW sebagai media dakwah T.G.K.H. Muhammad Zainuddin Abdul Madjid atas restu dari guru besar beliau yaitu Maulanasyaikh Hassan Muhammad Al-Masyath. Setelah dipadukan dengan kajian Semiotika Charles S.Peirce, keberadaan lambang NW telah sesuai dengan prinsip Semiotika dan jabaran makna lambang NW ini telah ditemukan dan teraplikasi pada bidang pendidikan, sosial dan dakwah Nahdlatul Wathan. Kata kunci: Semiotika, Media Dakwah, Nahdlatul Wathan.